Knowledge sector dimension of turkish economy - Düzgün, Burcu (My University, 2008)
Dünya ekonomisinde son yıllardaki sosyal ve teknolojik değişmeler mikro ve makro düzeyde bir çok yeniliği beraberinde getirmiştir ve bu değişim “bilgi ekonomisi” ile adlandırılmaktadır. Yeni ekonomi içinde bilgi büyük önem taşımaktadır. Ayrıca son birkaç on yılda gözlemlenen bu süreç ekonomilerin yeniden biçimlenmesine yol açmıştır. Yeni teknolojiler ve araştırmalar yeni bilgi olanakları doğurmuş ve bilişim sektörü bu yeni ekonominin lokomotifi haline gelmiştir. Böylece toplumlar daha bilgiye dayalı hale dönüşme sürecine girmişleridir. Bu değişim bağlamında bu çalışmanın amacı iki soru etrafında toplanmaktadır. Bunlardan ilki, Türkiye’de istihdamın bilgi yoğun sektörlere ve bilgi yoğun mesleklere kaymakta olup olmadığını incelemektedir. Bu bağlamda sektörlerler arası istihdam değişmeleri, bu sektörlerin bilgi yoğunlukları, bilgiye dayalı mesleklerin oranı ve işçilerin eğitim düzeylerindeki değişim araştırılmıştır. Türkiye’de servis sektöründeki ve bilgiye dayalı istihdamdaki artışa rağmen imalat sanayinin istihdamdaki artışını sürdürdüğü görülmüştür. Aynı zamanda orta bilgi yoğun sektörler istihdamda daha büyük bir paya sahiptir. İkinci soru Türkiye’de bilişim teknolojilerinin kullanımını araştırmaya yöneliktir. Bu araştırma için Türkiye’nin bilişim teknolojileri endekslerindeki sıralamasına ve başlıca bilişim teknolojileri kullanım oranlarına bakılmıştır. Bilişim teknolojileri kullanımında son yıllarda görülen artışa rağmen, Türkiye hala gelişmiş ülkelerin gerisinde yer almaktadır.

Social and technological changes in recent years in world's economy has changed many factors in both micro and macro level and has been explained by the expression “knowledge economy” in which knowledge has a critical importance. The ongoing process has been observed, especially in last couple of decades, in a manner to form new configuration of the economies. New technologies and researches create new information possibilities which in turn transform the societies into more knowledge based socities and ICT sector has become the locomotive of new economy in the world. In this context, the aim of this study is to analyze the dimesion of the knowledge sectors with two main questions. First question addresses the shift of employment towards knowledge intensive industries and knowledge occupations in Turkey. In this sense, sectoral shifts among basic business industries, knowledge intensity of those industries with the scope of knowledge employment in Turkey by presenting changes in occupational structure and educational attainment of workers are examined. It was found that although there is an increase in knowledge and services employment, manufacturing employment also continues to grow in Turkey and middle knowledge intensity sectors shows the largest employment growth over the analyzed period. Second question addresses ICT utilization in the light of newly implemented projects in Turkey. The ranking of Turkey in basic ICT indexes and the ratio of ICT usage by households and businesses is analyzed and it was found that, despite the increase in utilization of main ICTs, Turkey is still behind usage level in developed countries.
Keywords: Türkiye_Ekonomi